Sustainability Communication by Patagonia for Green Economic Growth - Aditia, Rafinita; Trung, Phan Nhan; Alfisyahri, Nuriah (Jurnal ILMU KOMUNIKASI, 2025)
Abstract: This study examines how Patagonia's "1% for the Planet" campaign utilizes communication narratives to promote sustainability and encourage global green economic growth. By applying Charles Sanders Peirce's semiotics framework icon, index, and symbol the study evaluates how effectively Patagonia communicates environmental conservation and aligns it with consumer behavior and corporate responsibility. A qualitative approach was employed, analyzing visual and textual elements from Patagonia's campaign materials, including advertisements, social media posts, and website content. The study findings show that Patagonia adeptly integrates semiotic elements to craft a compelling sustainability narrative.